2003
DOI: 10.1002/hyp.1251
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of water fluxes in a residential area: 2. Road infiltration, runoff and evaporation

Abstract: Abstract:Lack of accurate data has led some hydrologists and city planners to assume that urban infiltration is zero and runoff is 100% of the rainfall. These assumptions lead to an over estimation of road runoff volume and an underestimation of direct recharge to groundwater, which is already rising under some UK cities. This study investigates infiltration and runoff processes and quantifies the percentage of rainfall that contributes to storm drainage, and that which infiltrates through different types of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 15 publications
4
70
0
Order By: Relevance
“…Ragab et al (2003) presented an experimental study of water fluxes in a residential area, in which they estimated infiltration and evaporation in urban areas, showing that the assumption that all rainfall becomes runoff is not correct and that it leads to an overestimation of runoff. Ramier et al (2011) studied the hydrological behaviour of urban streets over a 38-month period to estimate runoff losses and to better define rainfall runoff transformations.…”
Section: Infiltration Interception and Storagementioning
confidence: 99%
See 3 more Smart Citations
“…Ragab et al (2003) presented an experimental study of water fluxes in a residential area, in which they estimated infiltration and evaporation in urban areas, showing that the assumption that all rainfall becomes runoff is not correct and that it leads to an overestimation of runoff. Ramier et al (2011) studied the hydrological behaviour of urban streets over a 38-month period to estimate runoff losses and to better define rainfall runoff transformations.…”
Section: Infiltration Interception and Storagementioning
confidence: 99%
“…The presence of leakage from drinking water and sewer networks can increase infiltration to groundwater and amount of contaminants that is spread from the sewer system into the soil (Salvadore et al, 2015). Although it is well known that not all rainfall turns into runoff (Boogaard et al, 2013;Lucke et al, 2014), it is common to consider the losses from impervious areas so small that they can be assumed negligible compared to the total runoff volume (Ragab et al, 2003;Ramier et al, 2011). Ragab et al (2003) tried to emphasize the importance of ac-counting for infiltration in the urban water balance, and found that infiltration through the road surface can constitute between 6 and 9 % of annual rainfall.…”
Section: Groundwater Recharge and Subsurface Processes In Urban Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…Imperviousness of urban areas is, however, very heterogeneous. Infiltration of impervious areas may not always be zero (Ragab et al, 2003). Impervious areas that are directly connected to the receiving river have a much larger effect on that receiving river (Boyd et al, 1994;Walsh et al, 2009).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%